2020
DOI: 10.3390/sym12040662
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Candidates with Dark Energy Interiors Determined by Energy Conditions

Abstract: We outline the basic properties of regular black holes, their remnants and self-gravitating solitons G-lumps with the de Sitter and phantom interiors, which can be considered as heavy dark matter (DM) candidates generically related to a dark energy (DE). They are specified by the condition T t t = T r r and described by regular solutions of the Kerr-Shild class. Solutions for spinning objects can be obtained from spherical solutions by the Newman-Janis algorithm. Basic feature of all spinning objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Analysis of spherically symmeric Einstein equations has shown that regular solutions of the Kerr-Schild class, specified by ( 1) and described by the merics (2), have obligatory de Sitter centers [7,67]. Repulsive gravity of the de Sitter vacuum prevents the formation of a singularity in accordance with the early hypothesis of a geometry self-regulation [68], of the existence of the limiting value of spacetime curvature [69], of spacetime symmetry restoration on the GUT scale [20,70,71]-confirmed later in the frame of quadratic gravity [72]-of renormalization group improvement [73], of non-commutative geometry approach [74], and of an ultraviolet quantum gravity [75,76] (for a recent review, see [25,77]).…”
Section: Dm Candidates With the De Sitter Vacuum Interiorssupporting
confidence: 59%
See 2 more Smart Citations
“…Analysis of spherically symmeric Einstein equations has shown that regular solutions of the Kerr-Schild class, specified by ( 1) and described by the merics (2), have obligatory de Sitter centers [7,67]. Repulsive gravity of the de Sitter vacuum prevents the formation of a singularity in accordance with the early hypothesis of a geometry self-regulation [68], of the existence of the limiting value of spacetime curvature [69], of spacetime symmetry restoration on the GUT scale [20,70,71]-confirmed later in the frame of quadratic gravity [72]-of renormalization group improvement [73], of non-commutative geometry approach [74], and of an ultraviolet quantum gravity [75,76] (for a recent review, see [25,77]).…”
Section: Dm Candidates With the De Sitter Vacuum Interiorssupporting
confidence: 59%
“…The mass of regular remnants with the de Sitter vacuum at the GUT scale is estimated as 10 2 -10 3 g [20]. Therefore, remnants, G-lumps and graviatoms are classified as heavy DM candidates with DE interiors (for a review, see [25]).…”
Section: Observational Signatures Of Remnants and G-lumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also regular black hole models which have been considered as dark matter candidates (see Refs. [17,18] for very recent reviews on the subject), including extremal configurations [19]. In particular, regular black hole remnants, G-lumps and graviatoms can be considered heavy dark matter candidates with dark energy interiors [20] which can induce observational consequences, such as proton decay [21].…”
Section: Introduction and Purpose Of The Workmentioning
confidence: 99%
“…Very recently, regular black holes with a Minkowski core have been recently reported [15], allowing thus to explore new possibilities such as the construction of thin-shell traversable wormholes [16]. There are also regular black hole models which have been considered as dark matter candidates (see [17,18] for very recent reviews on the subject), including extremal configurations [19]. In particular, regular black hole remnants, G-lumps and graviatoms can be considered heavy dark matter candidates with dark energy interiors [20] which can induce observational consequences, such as proton decay [21].…”
Section: Introduction and Purpose Of The Workmentioning
confidence: 99%